The influence of zoledronate and teriparatide on gamma delta T cells in mice - Eiki Yamachika; Yuichi Matsui; Masakazu Matsubara; Tatsushi Matsumura; Naoki Nakata; Norifumi Moritani; Atsushi Ikeda; Hidetsugu Tsujigiwa; Naoya Ohara; Seiji Iida (Elsevier, 2017)
Background/purpose: Few studies have investigated the possibility that bisphosphonate-related osteonecrosis of the jaw (BRONJ) might reflect an immune response; however, gamma delta T cells have been shown to significantly decline in the blood of BRONJ patients. Additionally, there have been some reports of teriparatide usage for the treatment of BRONJ. In this study, we compared the effects of zoledronate and teriparatide on lymphocyte populations and inflammatory cytokine production in mice. Materials and methods: Thirty female ICR mice were divided into three groups (n = 10 each): a vehicle, a zoledronate, and a teriparatide group. Drugs were administered for 8 weeks in each group. Lymphocytes in the blood and thymus were analyzed and femurs were used for histological observation and lymphocytes analysis of bone marrow. Cytokines were measured in separated serum using Milliplex® multiplex immunoassay analysis. Results: Zoledronate decreased the T cell number in the bone marrow. Additionally, serum levels of interleukin (IL)-2, IL-7, IL-12, IL-15 and RANTES, which are cytokines that affect T cell activation, differentiation and/or proliferation, were significantly lower in zoledronate treated mice. Conversely, teriparatide treatment induced an increase in gamma delta T cells in peripheral blood. Conclusion: Gamma delta T cells in the bone marrow are expected to decrease with zoledronate treatment and increase with teriparatide treatment. If BRONJ involves a loss of gamma delta T cells in the circulation or bone marrow, then the increase in gamma delta T cells that is induced by teriparatide may account for its ability to resolve BRONJ. Keywords: bisphosphonate, BRONJ, zoledronate, teriparatide, gamma delta T cell